Effect of four inert dusts on some biological aspects of Khapra beetle Trogoderma granarium Everts (Coleoptera: Dermestidae) - Ali Almimari; Ibrahim Alhadidy (College of Education for Pure Sciences, 2021)
In this study four types of inert dusts were mixed with wheat grains at three concentrations 5, 7 and 9 gm/kgm of wheat to estimate their effect on some biological aspects of Khapra beetle Trogoderma granarium Everts. These inert dusts are Chalky limestone, Bituminous limestone, Sand and Celite.             The results indicated that these inert dusts affected on some biological aspects of this insect, present results showed that the inert dusts caused death to larvae and pupae during its growth and development, and this led to reduce the number of insects, mortality rate of larvae increased to 46.64, 55.56, 27.78 and 87.78% for Chalky limestone, Bituminous limestone, Sand and Celite , respectively, as compared to 0.0% for the control. Also mortality rate of pupae increased to 15.02, 23.89, 3.69 and 27.77%, respectively, as compared to 0.0% for the control. This inert dusts led to significant increase of the larval period whereas were 30.05, 31.69, 27.41 and 33.85 day, respectively, as compared to 24.07 day for the control. Also inert dusts led to significant decrease of the emerging adults number whereas were 4.56, 3.56, 6.44 and 2.67 insect, respectively, as compared to 10.0 insect for the control, also inert dusts led to significant decrease of the laid eggs number whereas were 16.56, 16.44, 20.89 and 17.67 egg/ female, respectively, as compared to 34.67 egg/ female for the control.